2001
DOI: 10.4049/jimmunol.167.1.366
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 Production in Human Lung Fibroblasts and Epithelial Cells Activated by the Pseudomonas Autoinducer N-3-Oxododecanoyl Homoserine Lactone Is Transcriptionally Regulated by NF-κB and Activator Protein-2

Abstract: The destructive pulmonary inflammation associated with Pseudomonas aeruginosa colonization is caused, in part, by the production of the chemokine IL-8, which recruits neutrophils into the lung. The Pseudomonas autoinducer, N-3-oxododecanoyl homoserine lactone (3-O-C12-HSL), is a small lipid-soluble molecule that is essential in the regulation of many P. aeruginosa virulence factors, but little is known about how it affects eukaryotic cells. In this report we demonstrate that 3-O-C12-HSL is a potent stimulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
212
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(227 citation statements)
references
References 53 publications
10
212
4
Order By: Relevance
“…The abilities of this Gram-negative bacterium to survive and establish chronic infections in the host appear to be associated with functions of C12 (20,21). Interestingly, C12 has also been reported to exhibit effects on eukaryotic cells (15,21) including inhibition of cell proliferation (22,23), induction of apoptosis (23,24), and nuclear translocation of NF-B (15,25). These observations suggest that C12 may function as a PAMP.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The abilities of this Gram-negative bacterium to survive and establish chronic infections in the host appear to be associated with functions of C12 (20,21). Interestingly, C12 has also been reported to exhibit effects on eukaryotic cells (15,21) including inhibition of cell proliferation (22,23), induction of apoptosis (23,24), and nuclear translocation of NF-B (15,25). These observations suggest that C12 may function as a PAMP.…”
mentioning
confidence: 80%
“…Consistent with the observation that SV40 large T antigen alters the functions of p53 (57, 61), we found that C12 induces Cox-2 mRNA in SV40-transformed WI-38 cells but not in primary cells. Analogous to C12-mediated transcriptional response in WI-38 cells, Cox-2 and IL-8 induction was previously observed after C12 treatment of immortalized or transformed human epithelial cells and lung fibroblasts (25,62). Although the integrity of p53 was not tested in these cells, immortalization and transformation may be a result of mutations in the p53 gene (57,61).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its quorum-sensing function, the P. aeruginosa N-3-oxododecanoyl-homoserine lactone (3-oxo-C 12 -HSL) autoinducer has been suggested to modulate the immune responses of the infected host. In this context, it was demonstrated that 3-oxo-C 12 -HSL induces the production of interleukin-8 (IL-8), cyclooxygenase 2, and prostaglandin E2 in human fibroblasts and that it accelerates apoptosis in mammalian macrophages and neutrophils (15,16,18).…”
mentioning
confidence: 99%
“…3O-C12 operates through TLR-and Nod/Ipaf/caterpillarindependent signaling to activate multiple proinflammatory genes that are associated with NF-B signaling, including IL8, Cox2, and MUC5AC in both epithelial and other cell types (7)(8)(9)(10)(11)(12). Some of these proinflammatory effects may be mediated through activation of MAPKs (8,9) or Ca 2ϩ (7,13) or inhibition of peroxisome proliferator-activated receptor ␥ (14).…”
mentioning
confidence: 99%